Maternal Health Beliefs, Perceptions, and Experiences in a U.S. Marshallese Community. (March 2020) - Ayers, Britni L.; Purvis, Rachel S.; Bing, Williamina Ioanna; Ritok, Mandy; Iban, Anita; Capelle, Lucy; Hawley, Nicola L.; Delafield, Rebecca; McElfish, Pearl A.
Introduction: The purpose of this article is to review the beliefs, perceptions, and experience of maternal health among Marshallese women.Methodology: The study utilized a qualitative descriptive design with a brief survey of participant demographics. A purposive sample of 43 participants were enrolled.Results: The mean age of participants was 40 years. Four a priori themes were identified as follows: (a) family planning beliefs and experiences, (b) prenatal beliefs and experiences, (c) birthing beliefs and experiences, and (d) postpartum beliefs and experiences.Discussion: This study identified beliefs, perceptions, and experiences among Marshallese that have implications for policy and practice related to culturally congruent health care for Marshallese mothers.